(untitled) (Communications in Mathematical Research, 2019)
Applying the Nevanlinna theory of meromorphic function, we investigate the non-admissible meromorphic solutions of nonlinear complex algebraic differential equation and gain a general result. Meanwhile, we prove that the meromorphic solutions of some types of the systems of nonlinear complex differential equations are non-admissible. Moreover, the form of the systems of equations with admissible solutions is discussed.